2022
DOI: 10.3389/fpsyt.2022.878960
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between POMC rs2071345 Polymorphism and Alcohol Dependence in Anxiety Symptoms Among Chinese Male Problem Drinkers

Abstract: ObjectiveAlcohol dependence can increase the level of anxiety. A growing body of research has identified a link between anxiety symptoms of problem drinkers and their genetic or environment factors, respectively. However, to date few studies have directly examined gene-environment (G × E) interaction on their anxiety symptoms during the acute alcohol withdrawal. The present study aims to examine the interaction between the proopiomelanocortin (POMC) rs2071345 polymorphism and alcohol dependence on anxiety symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Consistent with previous studies (35,36), we found that anxiety and depression symptoms during withdrawal in AUD patients are highly correlated with alcohol dependence levels in withdrawal. There is an established relationship between alcohol and anxiety; high anxiety levels in AUD patients manifest during alcohol withdrawal (37-39).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (35,36), we found that anxiety and depression symptoms during withdrawal in AUD patients are highly correlated with alcohol dependence levels in withdrawal. There is an established relationship between alcohol and anxiety; high anxiety levels in AUD patients manifest during alcohol withdrawal (37-39).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we re-analyzed the data to explain how alcohol use influences these results. As shown in Supplementary Table 1, MAST scores were positively correlated with SAS scores (r = 0.36, p < 0.001), suggesting that anxiety was positively correlated with alcohol dependence, as our previous study reported [36]. However, there is no significant correlation between polymorphisms of rs266729 and MAST scores (r = 0.003, p > 0.05).…”
Section: No Interactive Effect Of Alcohol Dependence and Adpn Rs26672...mentioning
confidence: 54%